Okhotsk Sea ice as a reservoir of Listeria monocytogenes - Terekhova,Valeriya E.; Buzoleva,Liubov S.; Sosnin,Valeriy A.; Shakirov,Renat B.; Biebow,Nicole; Obzhirov,Anatoly I.; Terekhov,Evgeniy P.; Shoji,Hitoshi; Somov,George P. (National Institute of Polar Research, 2006)
P(論文) The contamination of sea ice by Listeria monocytogenes was investigated in the western part of the Sea of Okhotsk for the first time. The influence of the Amur River outflow on Listeria's distribution on the northeastern Sakhalin shelf and slope is discussed. Laboratory investigations of the survival of L. monocytogenes in frozen seawater are provided as well. It is possible to characterize the temporal evolution of the reproductive function of L. monocytogenes in sea ice. The duration of Listeria's reproductive period in sea ice depends on the strain's biological peculiarities and on the temperature regime. Colder temperatures result in a long-term reproductive ability of L. monocytogenes in sea ice. departmental bulletin paper